1989
DOI: 10.1185/03007998909115934
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of etodolac in the treatment of osteoarthritis

Abstract: An open clinical trial was carried out in 57 patients with osteoarthritis of the knee, hip or spine to assess the effectiveness and tolerability of etodolac. Patients received 200 mg etodolac twice daily for a period of 2 weeks. The results of clinical and patient assessments made at baseline and at the end of the study period showed that there was significant improvement in pain at rest and on active and passive movement, local tenderness, pain on climbing stairs, joint swelling and functional status. No sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…In standard animal models, etodolac has demonstrated a therapeutic index (antiinflammatory effects to gastric irritation) that is superior to that of indomethacin, phenylbutazone and naproxen 8 . In humans, etodolac has been shown to improve the symptoms of postsurgical pain, 9 , 10 rheumatoid arthritis (RA) 11–14 and OA 15–21 . Previous studies have shown that etodolac compares favourably with other NSAIDs commonly used in the treatment of OA 17–21 and RA 12 and that it appears to have a satisfactory safety profile 13–15 , 22–24 .…”
mentioning
confidence: 99%
“…In standard animal models, etodolac has demonstrated a therapeutic index (antiinflammatory effects to gastric irritation) that is superior to that of indomethacin, phenylbutazone and naproxen 8 . In humans, etodolac has been shown to improve the symptoms of postsurgical pain, 9 , 10 rheumatoid arthritis (RA) 11–14 and OA 15–21 . Previous studies have shown that etodolac compares favourably with other NSAIDs commonly used in the treatment of OA 17–21 and RA 12 and that it appears to have a satisfactory safety profile 13–15 , 22–24 .…”
mentioning
confidence: 99%